GUIDELINES FOR MAKING ANNUAL OPERATION PLAN BASE ON GOOD GOVERNANCE FOR SCHOOL IN EDUCATION NETWORK CENTER 5 JATUPOOM SRIWICHAI, UNDER NAKHON SI THAMMARAT PRIMARY EDUCATIONAL SERVICE AREA OFFICE 2 - Kokathing, Onamon; Onkone, Samit; Sumato, Phamshssupot (Journal of MCU Nakhondhat, 2023)
The objectives of this research are: 1) to study the condition of making annual operation plan for school. 2) to study guidelines for making annual operation plan base on good governance for school. 3) to present the guidelines for making annual operation plan base on good governance for school. The study was qualitative research. Data were collected via in- depth interviews with 15 people involved, 5 key informants, and focus group discussion by 7 experts for analytic induction. The results of the study revealed that: The status of the preparation of the annual action plan for school has a scope of operation in 5 steps, consisting of 1) there is an analysis of the educational quality development plan for 3-5 years. 2) estimated income of schools. 3) estimated expenditures of schools. 4) analyze and determine the project according to the strategic plan. 5) drafting an action plan. 2) The guidelines for making annual operation plan base on good governance consist of 5 steps which are as follows 1) there is an analysis of the educational quality development plan for 3-5 years according to good governance. 2) estimated income of schools according to good governance. 3) estimated expenditures of schools according to good governance. 4) analyze and determine the project according to the strategic plan according to good governance. 5) drafting an action plan according to good governance. 3) The experts verified the guidelines for making annual operation plan base on good governance for school in education network center 5 Jatupoom Sriwichai under Nakhon Si Thammarat Primary educational service area of office 2 and found that regarding the focus group discussion, the guidelines have suitability, possibility and usefulness which can be applicable.